Maternal age at first childbirth and under-five morbidity in sub-Saharan Africa: analysis of cross-sectional data of 32 countries - Bright Opoku Ahinkorah (BMC, 2021)
Abstract Background The prevalence of childhood morbidity remains high in low-and middle-income countries, including sub-Saharan Africa (SSA). In this study, the association between maternal age at first childbirth and under-five morbidity in SSA was examined. Methods This was a cross-sectional study involving nationally-representative data from the most recent Demographic and Health Surveys conducted in 32 countries in SSA from 2010 to 2019. A sample size of 311,603 mothers of children under-five was considered. The outcome variable for this study was under-five morbidity. This variable was derived from the experience of fever, cough, and diarrhoea among children under-five. Both multilevel and binary logistic regression models were used to test the hypothesis that adolescent childbirth is associated with under-five morbidity. The results were presented as crude odds ratios (cORs) and adjusted odds ratios (aORs), with 95 % confidence intervals (CIs). Results Children born to mothers whose first childbirth occurred at < 20 years were 16 % times more likely to suffer from under-five morbidity, compared to those whose mothers' first childbirth occurred at age ≥ 20 years [cOR = 1.16; CI = 1.13-1.19], and this persisted but with reduced odds after controlling for covariates [aOR = 1.10; CI = 1.07-1.12]. At the country level, children born to mothers whose first childbirth occurred at < 20 years were more likely to suffer from under-five morbidity, compared to those whose mothers' first childbirth occurred at age ≥ 20 years in Angola, Burundi, Congo DR, Guinea, Kenya, and Uganda. Conclusions In this study, an association between adolescent childbirth and morbidity in children under five in SSA has been established. The study concludes that under-five morbidity is higher among children born to mothers whose first childbirth occurred before 20 years compared to those whose mothers' first childbirth occurred at 20 years and above. The findings indicate that in order to reduce under-five morbidity, there is the need to deal with adolescent childbearing through cultural and social change, coupled with engagement of adolescents and stakeholders in adolescent sexual and reproductive health programmes.